Obliteration in the Holy Quran - Al-aqeel, Aishah Ali (Journal of Islamic Sciences, 2020)
Research aimed to know the sections of (Obliteration) and meanings of sensory and moral obliteration، and finding out the cause of prophet ’ Moses’ and understanding the meanings of the obliteration of the funds، blinding the eyes، blurring the stars and finding out the reason for the obliteration of the abattoir and identifying the causes of the obliteration and its effects. I followed the word (Obliteration) in the Holy Quran، gathering the verses in which the word is mentioned، and taking note of its interpretation، and then attempts to derive the meanings of the word through the use of the Holy Quran. Researcher summarize the most important results as the following: (Obliteration) has two meanings: sensory and moral، and that the meaning of sense of three meanings and the meanings of five meanings، The word "faces" comes with tow meanings in the Quran: the meaning of the object of the face and the meaning of intent and intention. The relationship between them lies in that if a person cuts off a good person، he walks and turns towards him in his face. The recommendations are: the reader of Quran comply with the commands of the Quran and avoid its intentions، and that away from the causes of obliteration and Train the soul to meditate and reflect on the verses of God bequeathed the servant to maximize God، as it helps to develop the perception and the ability to absorb and understanding properly.